2016
DOI: 10.1051/kmae/2016009
|View full text |Cite
|
Sign up to set email alerts
|

Status ofPseudorasbora parvain the Tiber River Basin (Umbria, central Italy) 20 years after its introduction

Abstract: -The aim of this research was to assess the distribution, abundance and growth of the non-native topmouth gudgeon Pseudorasbora parva that was recorded for the first time in the Tiber River Basin (central Italy) in 1994. The competitive interaction of P. parva with four native fish species was also investigated. The study area comprised 92 watercourses of the Umbrian section of the Tiber River Basin. Demographic and environmental data were collected during the period 1990−2014 in 171 sampling sites. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 32 publications
(42 reference statements)
2
16
2
Order By: Relevance
“…Similarly to previous studies [28,45], our CCA demonstrates how the fish species are distributed along the longitudinal gradient of the watercourses and which are the environmental variables that most influence their distribution. As reported for other watersheds in the Mediterranean area [70], also in the Tiber River basin the longitudinal gradient was associated with a progressive decline in water quality, proceeding from upstream to downstream, demonstrated by the decrease of EBI and increased conductivity and concentration of dissolved salts.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Similarly to previous studies [28,45], our CCA demonstrates how the fish species are distributed along the longitudinal gradient of the watercourses and which are the environmental variables that most influence their distribution. As reported for other watersheds in the Mediterranean area [70], also in the Tiber River basin the longitudinal gradient was associated with a progressive decline in water quality, proceeding from upstream to downstream, demonstrated by the decrease of EBI and increased conductivity and concentration of dissolved salts.…”
Section: Discussionsupporting
confidence: 69%
“…were derived from digital maps (geographic information system (GIS)) provided by the Forest, Economics and Mountain Territory Service of the Umbria Region. In order to evaluate water quality based on the presence of macro-invertebrates, the Extended Biotic Index (EBI) was used [44] (for more details, see [45]). To examine the opportunity for fish species to move upstream, the presence of dams and weirs located in the hydrographic network were detected and their geographical coordinates were derived using a GARMIN global positioning system (GPS) map 62 s with accuracy <10 m. The river fragmentation degree has been codified as the number of weirs with height >80 cm present downstream of each sampling site, up to the main receptor watercourse.…”
Section: Data Collectionmentioning
confidence: 99%
“…Previous research carried out on fish communities inhabiting the Tiber river basin (central Italy) have shown that most of alien freshwater fish have been introduced over the last 30 years through restocking activities in favor of recreational fishery [20]; they have been initially released in multiple sites, and subsequently expanded their range using the connections of the hydrographic network [24]. Some of these species, as Barbus barbus (Linnaeus, 1758), Gobio gobio (Linnaeus, 1758), Padogobius bonelli (Bonaparte, 1846) and Pseudorasbora parva (Temminck & Schlegel, 1846), immediately after their introduction occurred in the period between 1993 and 1999, quickly acclimatized and are currently present with many self-sustaining populations [25,26]. Worryingly, the spread of these invasive species has contributed to the local extinction or range shift of some endemic ones.…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies on various features of P. parva at national and international (Erk'akan, 1984, Wildekamp et al, 1997, Cakic et al, 2004, Ekmekçi & Kırankaya, 2006Britton et al, 2007;Boltachev, 2006;Karabanov et al, 2010;Wang et al, 2012;Patimar & Baensaf, 2012;Huo et al, 2012;Tarkan et al, 2014;Kırankaya et al, 2014;Kapusta et al, 2014;Tarkan et al, 2015;İlhan & Sarı 2015;Carosi et al, 2016;Benzer et al, 2016;Bakaç et al, 2017;Benzer 2018;Benzer & Benzer 2019) in the different locations. This paper describes the area where this fish was found and recorded morphometric data of the population in Hirfanlı Reservoir.…”
Section: Introductionmentioning
confidence: 99%